2012
DOI: 10.1590/s0101-20612012005000073
|View full text |Cite
|
Sign up to set email alerts
|

Processing and characterization of extruded breakfast meal formulated with broken rice and bean flour

Abstract: The objective of this work was to develop an extruded breakfast product containing broken rice and split old beans and to verify the influence of the extrusion process on their physicochemical, technological, and sensory characteristic. The final product had a protein content of 9.9 g.100 g-1, and therefore it can be considered a good source of proteins for children and teenagers. The dietary fiber content of the final edible product was 3.71 g.100 g-1. Therefore, the breakfast meal may be considered as a sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 33 publications
6
16
0
8
Order By: Relevance
“…The majority of consumers (53%) reported that they would certainly or possibly purchase the product if available on the market and a low level of rejection was observed (13%). The relevant acceptance index regarding purchase intention suggests an excellent market potential for the product devised in this study as previously found by Carvalho et al (2012) with a breakfast cereal prepared with extruded rice and bean flours.…”
Section: Sensory Analysissupporting
confidence: 69%
See 1 more Smart Citation
“…The majority of consumers (53%) reported that they would certainly or possibly purchase the product if available on the market and a low level of rejection was observed (13%). The relevant acceptance index regarding purchase intention suggests an excellent market potential for the product devised in this study as previously found by Carvalho et al (2012) with a breakfast cereal prepared with extruded rice and bean flours.…”
Section: Sensory Analysissupporting
confidence: 69%
“…The relevant acceptance index regarding purchase intention suggests an excellent market potential for the product devised in this study as previously found by Carvalho et al . () with a breakfast cereal prepared with extruded rice and bean flours.…”
Section: Resultsmentioning
confidence: 99%
“…In Mexico, whole wheat bread has been supplemented with 0.5% of freeze-dried black bean seed coat extract [102]. In Brazil, common bean flour has been added to rice flour and sugar in a proportion of 30:70:5%, respectively, to produce extruded breakfast flakes [103]. In Canada, a new bean snack, similar to pretzels, composed by 34% of navy bean flour has been developed.…”
Section: Innovative Food Productsmentioning
confidence: 99%
“…The drying process of the seeds have two phases, which have no specific designation, giving one in sequence the other. The first phase happens in the movement of the water contained in the surface of the seed to the surrounding air, happening through the process of evaporation and being subject to the factors that control this process, the second phase consists of the passage of water from the internal tissues of the seed to the surface (Carvalho & Nakagawa, 2012). This movement of the water molecules occurs by a process of capillarity and the mechanical obstacles in the way to be traveled by the molecules of water to the surface competes so that the second phase is slower than the first, also, as the seed dry, the drying becomes more time consuming (Carvalho, 2005).…”
Section: Introductionmentioning
confidence: 99%